Case Report: Ectopic CRH production by adrenal adenoma as a unique cause of the ACTH-dependent Cushing’s syndrome - Pokrzywa, Agata; Pachucki, Janusz; Bobrowicz, Małgorzata; Koperski, Łukasz; Ambroziak, Urszula (Frontiers in Endocrinology, 2025)
Isolated ectopic secretion of corticotropin-releasing hormone (CRH) is an exceedingly rare cause of Cushing’s syndrome (CS), accounting for fewer than 1% of cases. Ectopic CS is an uncommon but potentially life-threatening condition that often necessitates urgent diagnostic evaluation and treatment. Hormonal testing may suggest a pituitary origin, complicating the diagnostic process. To date, isolated ectopic CRH production has primarily been reported in cases of medullary thyroid carcinoma, pheochromocytoma, and various neuroendocrine tumors. We present the first documented case of adrenocorticotropic hormone (ACTH)-dependent CS resulting from CRH secretion by an adrenal cortical adenoma. A 68-year-old woman presented with severe hypercortisolemia and biochemically confirmed ACTH-dependent CS. Imaging revealed an unilateral adrenal mass without evidence of pituitary or extra-adrenal lesions. Dynamic endocrine testing was consistent with an ectopic source of ACTH. The patient underwent unilateral adrenalectomy, which led to full clinical and biochemical remission without prolonged adrenal insufficiency. Histopathological analysis confirmed an adrenal cortical adenoma showing focal immunoreactivity for CRH and absence of ACTH expression. This case highlights the importance of considering ectopic CRH secretion in the differential diagnosis of atypical ACTH-dependent CS, especially in patients presenting with adrenal adenomas.